Caring of Neurosurgical Patients with External Ventricular Drain - Mahat, Roshani; Moktan, Amita; Thapa, Sanskriti; Devkota, Ranju; Rajbhandari, Pravesh; pant, Basant (Annapurna Journal of Health Sciences, 2023)
An external ventricular drain (EVD), also known as a ventriculostomy or extraventricular drain, is a device used in neurosurgery to treat hydrocephalus which can lead to raised intracranial pressure when the normal flow of cerebrospinal fluid (CSF) inside the brain is obstructed. An EVD is a flexible plastic catheter placed by a neurosurgeon or neurointensivist and managed by intensive care unit (ICU) physicians and nurses. The purpose of external ventricular drainage is to divert fluid from the ventricles of the brain and allow for monitoring of intracranial pressure Nurses are responsible for the care of patients who have external ventricular drains. This article explains how the drains work and discusses key nursing considerations for their management.